Synthesis and Biological Characterization of a New Norbormide Derived Bodipy FL-Conjugated Fluorescent Probe for Cell Imaging - D'Amore, Claudio; Orso, Genny; Forgiarini, Alessia; Ceolotto, Giulio; Rennison, David; Ribaudo, Giovanni; Jay-Smith, Morgan; Hopkins, Brian; Brimble, Margaret A.; Bova, Sergio (Frontiers in Pharmacology, 2018)
Background. Norbormide (NRB) is a selective rat toxicant endowed with vasoconstrictor activity confined to the rat peripheral arteries. In a recent work we used a fluorescent derivative of NRB (NRB-AF12), obtained by coupling the NBD fluorophore to the parent molecule via a linker, in order to gain information about the possible site of action of the unlabelled compound. We found that NRB-AF12 labelled intracellular organelles in both NRB-sensitive and -insensitive cells and we accordingly proposed its use as a scaffold for the development of a new class of fluorescent probes. In this study, we examined the fluorescent properties of a BODIPY FL-conjugated NRB probe (MC009) developed: A) to verify if NRB distribution could be influenced by the attached fluorophore; B) to improve the fluorescent performance of NRB-AF12. Methods. MC009 characteristics were investigated by confocal fluorescence microscopy, in freshly isolated rat caudal artery myocytes (FIRCAM) and in LX2 cells, representative of NRB-sensitive and insensitive cells, respectively. Main results. In both FIRCAM and LX2 cells MC009 stained endoplasmic reticulum, mitochondria, Golgi apparatus and lipid droplets, revealing the same intracellular distribution as NRB-AF12, and, at the same time, had both improved photostability and gave a more intense fluorescent signal at lower concentrations than was possible with NRB-AF12, which resulted in a better and finer visualization of intracellular structures. Furthermore, MC009 was effective in cellular labelling in both living and fixed cells. At the concentration used to stain the cells, MC009 did not show any cytotoxic effect and did not affect the regular progression of cell cycle and division. Conclusions. This study demonstrates that the distribution of fluorescently labelled NRB is not affected by the type of fluorophore attached to the parent compound, supporting the idea that the localization of the fluorescent derivatives may reasonably reflect that of the parent compound. In addition, we observed a marked improvement in the fluorescent properties of BODIPY FL-conjugated NRB (MC009) over its NBD-derived counterpart (NRB-AF12), confirming NRB as a scaffold for the development of new, high performance, non-toxic fluorescent probes for the labelling of intracellular structures in both living and fixed cells.